Congestion control strategies for increased renewable penetration of photovoltaic in LV distribution networks. (December 2022) - Shabbir, Noman; Kutt, Lauri; Astapov, Victor; Husev, Oleksandr; Ahmadiahangar, Roya; Wen, Fushuan; Kull, Karl
Abstract: Domestic photovoltaic (PV) installations are increasing their spread due to decreased cost, environmental friendliness, and relatively easy installation. However, the massive domestic PV deployment can bring the LV network (LV) distribution network to its sustained operating limits, as overvoltage and congestion can arise. The overvoltage problems can emerge due to reverse power flows and congestion can be caused if the installed PV capacity is higher than the distribution line loading capacity. The limitations of the LV networks arise especially during the seasons when domestic power demand is minimal, and PVs are generating at their peak. The research presented here incorporates a real suburban LV network with fifteen residential users. The measured load and PV generation data for one year are used to carry out power flow simulations. Several congestion leveraging strategies such as battery energy storage system (BESS) incorporation, reactive power control (RPC), and curtailment of peaks are discussed.